Pendampingan Digitalisasi dan Implementasi Model Pembelajaran untuk Sekolah Dasar - Petrus Murwanto; Stefanus Setyo Wibagso; Ria Triayomi; Agnes Fibriana Kurniawati; Dewi Sri (CV. Creative Tugu Pena, 2025)
The article aimed giving an assistance digitalization and implementation of learning models for elementary schools. The community service activities conducted for elementary school teachers at St. Agatha Palembang. The participants in this activity were 16 teachers, the majority of whom were senior teachers and women. This assistance ensure that elementary schools can be better prepared to face the demands of modern education and produce a generation ready to face global challenges in the future. The service method consists of four stages: preparation, implementation, evaluation, and reporting. As a result of this service activity, the level of participant satisfaction with assistance activities was the highest, namely 50.4%, with answers strongly agreeing and 42.8% agreeing, which provided increased professionalism and insight for participants. This assistance has contributed, including supporting teacher freedom in creating learning innovations that suit student needs. Increasing student competence and helping students think creatively, collaborate, solve problems, and communicate aligns with strengthening the Pancasila Student Profile. This mentoring activity can also help teachers provide practical strategies for compiling interesting and relevant project-based material.